(untitled) (Mustansiria Dental Journal, 2018)
This Study represents an attempt to investigate histologically the effect of metallic mercury vapor on the developing rat teeth after inhalation by pregnant rats . In this study albino – wistar rats were used and divided into control and experimental groups. The control group consisted of 8 pregnant rats, and the experimental group consisted of 12 pregnant rats. Then 20 born rats from the control group and 20 born rats from the experimental group were selected to be sacrificed at the ages of (3&13) days. The specimens were prepared for processing and staining with haematoxylin and eosin, and examined under light microscope. Results showed no histological abnormalities in the dental tissue of the experimental group when compared to that of the control group .